2019
DOI: 10.1001/jamafacial.2018.1639
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Measurement Properties of Patient-Reported Outcome Measures After Rhinoplasty

Abstract: IMPORTANCEThe number of available rhinoplasty outcome measurement instruments has increased rapidly over the past years. A large heterogeneity of instruments of different quality now exists, causing difficulty in pooling and comparing outcome data. OBJECTIVE To critically appraise, summarize, and compare the measurement properties of all patient-reported outcome measures (PROMs) that measure functional or aesthetic symptoms of patients undergoing rhinoplasty, using consensus-based methodology and guidelines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…This is further supported by a recent systematic review of 33 studies that utilised 12 different measurement tools; the authors reported that the FACE-Q and the Standardized Cosmesis and Health Nasal Outcomes Survey aesthetic subscale were the best measures of outcomes in aesthetic surgical procedures. 30…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by a recent systematic review of 33 studies that utilised 12 different measurement tools; the authors reported that the FACE-Q and the Standardized Cosmesis and Health Nasal Outcomes Survey aesthetic subscale were the best measures of outcomes in aesthetic surgical procedures. 30…”
Section: Discussionmentioning
confidence: 99%
“…1) was created specifically to aid surgeons in assessing both nasal obstruction symptoms and nasal cosmesis in rhinoplasty patients. Among the quality-of-life (QOL) instruments' currently available for both aesthetic and functional rhinoplasty, the SCHNOS, which has been developed with a robust development technique, 3 is more precise, 2 more comprehensive, 4 and has been the most extensively validated. [5][6][7][8][9][10] The SCHNOS-O can be utilized as both a clinical and a screening tool for nasal obstruction, and the SCHNOS-C is a reliable clinical tool for cosmetic outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…6 As a specific patient reported measure of nasal obstruction it is validated for both septoplasty and septorhinoplasty 6,8,9 and van Zijl et al identified it as the most suitable PROM to measure functional outcomes. 10 Interestingly, the results of objective measures of obstruction often correlate poorly with subjective NOSE scores, and so the NOSE Scale is frequently the primary outcome measure for surgical treatment of nasal obstruction. 11 In the literature, there is limited normative data to provide perspective on the recent changes to MBS funding.…”
Section: Introductionmentioning
confidence: 99%